Citra Media Dan Kementerian Kesehatan Dalam Vaksinasi Covid 19 Di Makassar - Aulia Riski (Communicology: Jurnal Ilmu Komunikasi, 2022)
ABSTRACT This study aims to identify news regarding Covid-19 vaccination on the media portal detikcom edition 02 November 2021. The four stages of Framing Entman include: Define Problem, Diagnose Cause, Make moral judgment and Treatment recommendation. The framing analysis method used is how the media interpret, understand and frame the reported cases/events. This type of method tries to understand and interpret the meaning of the text naturally by explaining how the media frame the issue. The same event can be designed differently depending on the medium. The results show that Define Problem in the news is related to government policies in cooperating with the public to carry out vaccines, Diagnosis cause is shown in the form of the general public's indifferent attitude in responding to the Covid-19 pandemic prokes and vaccinations, Make moral judgment in the form of affirmation that the vaccination is a The important thing in suppressing the corona outbreak, and the treatment recommendation offered is that the government equips the media to report news on how important the Covid-19 vaccination is. Media as a means of forming an image, image is very important because the image can change the mindset of the audience about something. If an institution has a positive image then the public's mindset about the institution is also positive, but if the image that arises from the institution is negative then the mindset that appears in the community will also be negative. There are so many parties who use broadcast media as a means to raise a person's good name or image, with a specific purpose. So that online media is a public space that is considered important as a reference in improving people's information literacy, so that the news is expected to be more objective and educational. Keywords: Covid-19 Vaccination; Framing; News ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi pemberitaan mengenai vaksinasi Covid-19 di portal media detikcom edisi 02 november 2021. Empat tahap Framing Entmant mencakup: Define Problem, Diagnose Cause, Make moral judgment dan Treatment recommendation. Metode analisis framing yang digunakan adalah bagaimana media memaknai, memahami dan membingkai kasus/peristiwa yang diberitakan. Jenis metode ini mencoba memahami dan menafsirkan makna teks secara alami dengan menjelaskan bagaimana media membingkai isu. Acara yang sama dapat dirancang secara berbeda tergantung pada media. Hasil penelitian menunjukan bahwa Define Problem dalam pemberitaan berkaitan dengan kebijakan pemerintah dalam menggandeng para masyarakat untuk melakukan vaksin, Diagnose cause ditunjukkan dalam bentuk sikap acuh para khalayak umum dalam menanggapi prokes dan vaksinasi pandemi Covid-19, Make moral judgment dalam bentuk penegasan bahwa vaksinasi tersebut merupakan hal penting dalam penekanan wabah corona, dan treatment recommendation yang ditawarkan adalah pemerintah membekali media untuk memberitakan pemberitaan seberapa penting vaksinasi covid-19 tersebut. Media sebagai sarana pembentuk citra, citra merupakan hal yang sangat penting dikarenakan citra dapat mengubah pola pikir khalayak tentang suatu hal. Jika suatu lembaga memiliki citra positif maka pola pikir khalayak tentang lembaga tersebut juga positif namun apabila citra yang timbul dari lembaga tersebut negatif maka pola pikir yang muncul dimasyarakat juga akan negatif. Banyak sekali pihak-pihak yang menggunakan media penyiaran sebagai sarana mengangkat nama baik ataupun citra seseoarang, dengan tujuan tertentu. Sehingga media online merupakan ruang publik yang dianggap penting sebagai rujukan dalam meningkatkan literasi informasi masyarakat, sehingga pemberitaannya diharapkan agar lebih objektif dan mendidik. Kata Kunci: Berita; Framing; Vaksinasi Covid-19